LA FLORE DES MONTS D’AIN FEZZA DANS L’OUEST ALGERIEN, BIODIVERSITE ET DYNAMIQUE (Sciences & Technologie. C, Biotechnologies, 2007)
The vegetal rug is analysed by 02 principal factors wich are the bioclimate and the anthropic action. The impact of these 02 factors is widely expressed by a faster impover ishment and substitution of the vegetal cover species. This study shows the recolonization by non forested formation that are followed by a trivialization of the floristic thorny resources and / or toxic species. Dominated by the Mediterranean elements (54.38 %) and Nordic ones this flora relatively poor, (114 species altogether)  is biologically charaterized by a net abundance of therophytes (40.35 %), chamaephytes (21.50%) and hemicryptophytes (20.18%) to the detriment of phanerophytes (9.65%). The interpretation by the AFC of the vegetation (taxonomy) helped to precise the different taxons. This multidimensional treatement accentuates the importance of anthropic and bioclimatic factors that govern this dynamic